Synthesis of Chiral L2/Z-Type Ligands Featuring a Bisoxazoline Framework and Their Application to Palladium-Catalyzed Asymmetric Allylic Alkylation - Takahashi, Hikaru; Shibata, Takashi; Naito, Daisuke; Murakami, Ryo; Inagaki, Fuyuhiko (Synlett, 2024)
Chiral L2/Z*-type ligands featuring a bisoxazoline framework have been successfully synthesized and applied in asymmetric allylic alkylation. These ligands, designed based on an oxazoline skeleton and derived from chiral amino acid derivatives, incorporate antimony and bismuth as Z-type ligands. Ligands with bulky, electron-withdrawing groups on antimony and bismuth showed enhanced catalytic performance. This research highlights the potential of these novel chiral L2/Z*-type ligands to improve asymmetric catalysis.
Keywords: asymmetric catalyst; Z-type ligand; chiral oxazoline; transition metal; allylic alkylation